2019
DOI: 10.1016/j.ejrad.2019.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Radiology workflow for RECIST assessment in clinical trials: Can we reconcile time-efficiency and quality?

Abstract: Iannessi b a Median Technologies. 1800 route des crêtes, les deux arcs-Bat B. Sciences Department,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Our study gives encouraging results regarding the ability of some trained technologists to perform measurements according to RECIST 1.1 criteria during CT oncology follow-up with good identification of disease progression and excellent intra-observer reproducibility. Our results complement the study of Beaumont et al 28 , who showed in a cohort of 23 patients that the involvement of a specialized technician with specific computer tools required few corrections by radiologists (13%) and saved significant time for radiologists.…”
Section: Discussionsupporting
confidence: 90%
“…Our study gives encouraging results regarding the ability of some trained technologists to perform measurements according to RECIST 1.1 criteria during CT oncology follow-up with good identification of disease progression and excellent intra-observer reproducibility. Our results complement the study of Beaumont et al 28 , who showed in a cohort of 23 patients that the involvement of a specialized technician with specific computer tools required few corrections by radiologists (13%) and saved significant time for radiologists.…”
Section: Discussionsupporting
confidence: 90%
“…During the follow-up, the patients received both image evaluation, such as ultrasound, computed tomography, or magnetic resonance imaging and biochemical markers, such as CA-125 (the abbreviation of cancer antigen 125, carcinoma antigen 125, or carbohydrate antigen 125) examinations. The evaluation of image finding was based on Response Evaluation Criteria in Solid Tumors (RECIST), version 1.1 [127][128][129]. Criteria of progression or recurrence were based on findings of clinical symptoms or signs accompanied with image findings and tumor markers described elsewhere [41,130,131].…”
Section: Assessmentsmentioning
confidence: 99%
“…Multiple commercial products are currently available to assist in radiologic interpretation, standardized response assessment, and data management of imaging performed as part of an oncology clinical trial. Implementation of electronic case report forms during RECIST 1.1 interpretation was previously found to reduce nonconformity errors by 10-fold (43). Artificial intelligence is increasingly embedded within many of these platforms, including automation for tumor measurement, target and nontarget location labeling, tumor localization at follow-up, and response assessment categorization.…”
Section: Limitations and Futurementioning
confidence: 99%